Dangerous dining - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
The puffer fish is a famous type of fish in Japan. If it's prepared properly, it's a safe and delicious meal. If it's not, it can kill those who eat it. How do chefs prepare the fish correctly and what are scientist doing to protect people who eat puffer fish
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography